DEVELOPMENT ISSUES INTERACTIVE ELECTRONIC BOOK - Zhuran Е.А. (Journal of Information Technologies in Education (ITE), 2012)
This article examines trends in the development of teaching methods and problems faced by educational institutions and teachers in the development of interactive tutorials. The article highlights the priority areas of development in this field.